Restarting and recentering genetic algorithm variations for DNA fragment assembly: The necessity of a multi-strategy approach. (December 2016) - Hughes, James Alexander; Houghten, Sheridan; Ashlock, Daniel
Abstract: DNA Fragment assembly – an NP-Hard problem – is one of the major steps in of DNA sequencing. Multiple strategies have been used for this problem, including greedy graph-based algorithms, deBruijn graphs, and the overlap-layout-consensus approach. This study focuses on the overlap-layout-consensus approach. Heuristics and computational intelligence methods are combined to exploit their respective benefits. These algorithm combinations were able to produce high quality results surpassing the best results obtained by a number of competitive algorithms specially designed and tuned for this problem on thirteen of sixteen popular benchmarks. This work also reinforces the necessity of using multiple search strategies as it is clearly observed that algorithm performance is dependent on problem instance; without a deeper look into many searches, top solutions could be missed entirely.